2015
DOI: 10.1177/1403494815569105
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards human papillomavirus vaccination among Arab ethnic minority in Denmark: A qualitative study

Abstract: Educational programs should target both mothers and daughters because mothers have an inadequate knowledge about HPV. This is likely to bridge the gap of knowledge between mothers and daughters, which constitutes a barrier between the generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Twelve studies were conducted in the USA, three in the UK, one in the Netherlands, one in Denmark, one in Sweden, and one in Puerto Rico. Six studies were conducted in community organizations including faith-based centres like churches and mosques [21][22][23][24][25][26], eight in health and social service agencies [27][28][29][30][31][32][33][34], two in schools and/or community groups [35,36], another two in social clubs [37,38], and one in a household [39].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies were conducted in the USA, three in the UK, one in the Netherlands, one in Denmark, one in Sweden, and one in Puerto Rico. Six studies were conducted in community organizations including faith-based centres like churches and mosques [21][22][23][24][25][26], eight in health and social service agencies [27][28][29][30][31][32][33][34], two in schools and/or community groups [35,36], another two in social clubs [37,38], and one in a household [39].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 studies, 16 reported on knowledge of the immigrant parents about HPV vaccine (Table 2), 13 reported their attitudes (Table 3) and 10 recorded perceptions (as defined by study author) towards HPV vaccine (Table 4). Four studies reported knowledge and attitudes [21,27,30,37] and one reported knowledge and perceptions [26], seven studies reported on all three outcomes (knowledge, attitude and perceptions) [22,23,29,35,36,38,39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations